Single-Phase Commutator Motors and their Calculation Methods - Karaliūnas, B. (Elektronika ir Elektrotechnika, 2000)
There are analysed mathematical models, general equations and their solution numerical methods of electrical machines and commutator motors. It is proposed that equality of Parsewall may be used for colculation of electromagnetic force or moment. The new inductor desing of commutator motors was created and technical decision was recognized as invention.